Kegiatan Ecoprint Melatih Motorik Tangan Melatih Mata dan Meningkatkan Kreativitas Pada Lansia - Seriwati Ginting; Aulia Wara Arimbi Putri; Miki Tjandra; Monica Hartanti; Yunita Setyoningrum (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Elderly or old age is a human condition that has decreased body function and is characterized by increasingly limited physical activity. The decline in the quality of life of the elderly is due to the disease process (physiological) in the elderly. Indonesia is listed as one of the countries with the most elderly population in the world. This condition needs to get the attention of all parties so that the elderly can enjoy a quality life in their old age. The Faculty of Art and Design in collaboration with an elderly school under the auspices of Indonesia Ramah Lansia (IRL) Jawa Barat held a joint activity involving four schools for the elderly, with 120 participants. The activity chosen is ecoprint. Ecoprint is an activity that uses natural dyes made from tannins or colors found in plants, leaves, and flowers in its manufacturing process. Through this activity, elderly join together and work through it as a group by tapping evenly and rhythmically across the full surface of the cloth, which has been adorned with leaves or flowers of their choice. As a result, the color and shape of the leaves or flowers will stick to the fabric. A good ecoprint result is when the shape and color of the leaves or flowers stick to the original. On this occasion, the selected media is a strong calico cloth. The elderly are happy and cheerful to see their work. This activity also trains motoric skills in the hands, stimulates creativity, and increases immunity in the elderly.